Fear-Avoidance Beliefs in Chronic Cervical Zygapophyseal Joint Pain Relieve With Medial Branch Block - Farid Yudoyono (Indoscholar, 2018)
Background: Chronic posterior neck pain is common, affecting 50–75% of people for 1 year or longer. The zygapophyseal joint is reported to be one of most common causative factors. The fearavoidance is a model that describes how individuals develop chronic pain as a result of avoidant behaviour based on fear. Previous studies shown that medial branch block (MBB) and radio frequency neurotomy were effective for intractable pain. Material And Method: Case 1, TMK, Male, 57 yo, left posterior neck pain, VAS neck 7-8, NDI 46 %, no radiating pain, no neurological deficit. FABQ-PA score showed high fear (60%). Physical examination provokes facet joint pain. Neuroimaging revealed facet degeneration on T1WI and T2WI MRI. Case 2, RDW, Male, 45 yo, left posterior neck pain, VAS neck 8-9, NDI 40 %, no radiating pain, no neurological deficit. FABQPA score showed high fear (63%). Physical examination provokes facet joint pain. Neuroimaging revealed facet degeneration on T1WI and T2WI MRI. Case 3, TAY, Female, 52 yo, bilateral posterior neck pain, VAS neck 8-9, NDI 52 %, no radiating pain, no neurological deficit. FABQ-PA score showed high fear (60%). Physical examination provokes facet joint pain. Neuroimaging revealed facet degeneration on T1WI and T2WI MRI. Results: Our study reveals that C-MBB might ensure pain relief and decrease analgesic need. Physical activity at 1-, 3- and 6-months post-CMBB intervention were 65%, 60% and 68% of patients, respectively, gained > 50% pain relief. Conclusion: Therapeutic MBB may provide an option for chronic high fear-avoidance beliefs pain of zygapophyseal joint.